Antifungal potential of essential oil constituents (Research, Society and Development, 2021)
Natural products are important sources of discovery of new medicinal agents and, due to the biological and pharmacological potential of these compounds, it is necessary to carry out studies to enable their application. The objective of this work was to evaluate the antifungal potential of certain constituents of essential oils. The evaluation of the inhibitory effect of the compounds p-cimene, eugenol, carvacrol, citral, trans-caryophyllene and trans-farnesol was tested on the fungi Aspergillus carbonarius, Aspergillus flavus, Aspergillus ochraceus and Aspergillus niger, using the disk diffusion methodology. The effect of eugenol, carvacrol and citral compounds on the mycelial growth of A. carbonarius and A. niger fungi at different temperatures was evaluated. The analysis of the inhibitory activity of the fungi revealed that the compounds eugenol, carvacrol and citral showed greater capacity to inhibit the growth of the evaluated microorganisms. These constituents also influenced the mycelial growth of the fungi A. niger and A. carbonarius at different temperatures, with temperatures of 20 ºC and 25 ºC being more favorable for the development of the fungi. The results found proved to be promising in the search for bioactive compounds. Studies involving these constituents may be relevant in other activities, as well as in association with synthetic compounds already used in order to reduce their toxicity and resistance and assess the synergistic effect between them.